A double‐blind sham‐controlled phase 1 clinical trial of tDCS of the dorsolateral prefrontal cortex in cocaine inpatients: Craving, sleepiness, and contemplation to change. (18th March 2021) - Gaudreault, Pierre‐Olivier; Sharma, Akarsh; Datta, Abhishek; Nakamura‐Palacios, Ester M.; King, Sarah; Malaker, Pias; Wagner, Ariella; Vasa, Devarshi; Parvaz, Muhammad A.; Parra, Lucas C.; Alia‐Klein, Nelly; Goldstein, Rita Z.
Abstract: Impaired inhibitory control accompanied by enhanced salience attributed to drug‐related cues, both associated with function of the dorsolateral prefrontal cortex (dlPFC), are hallmarks of drug addiction, contributing to worse symptomatology including craving. dlPFC modulation with transcranial direct current stimulation (tDCS) previously showed craving reduction in inpatients with cocaine use disorder (CUD). Our study aimed at assessing feasibility of a longer tDCS protocol in CUD (15 versus the common five/10 sessions) and replicability of previous results. In a randomized double‐blind sham‐controlled protocol, 17 inpatients with CUD were assigned to either a real‐tDCS (right anodal/left cathodal) or a sham‐tDCS condition for 15 sessions. Following the previous report, primary outcome measures were self‐reported craving, anxiety, depression, and quality of life. Secondary measures included sleepiness, readiness to change drug use, and affect. We also assessed cognitive function including impulsivity. An 88% retention rate demonstrated feasibility. Partially supporting the previous results, there was a trend for self‐reported craving to decrease in the real‐tDCS group more than the sham‐group, an effect that would reach significance with 15 subjects per group. Quality of life and impulsivity improved over time in treatment in both groups. Daytime sleepiness and readiness to change drug use showed significant Group × Time interactions whereby improvements were noted only in the real‐tDCS group. One‐month follow‐up suggested transient effects of tDCS on sleepiness and craving. These preliminary results suggest the need for including more subjects to show a unique effect of real‐tDCS on craving and examine the duration of this effect. After replication in larger sample sizes, increased vigilance and motivation to change drug use in the real‐tDCS group may suggest fortification of dlPFC‐supported executive functions. Abstract : This randomized double‐blind phase 1 clinical trial showed a trend for a reduction in self‐reported craving in cocaine addicted individuals receiving real‐ versus sham‐tDCS of the right dorsolateral prefrontal cortex (dlPFC) 15 times over 5 weeks, supporting previous results. There was also a significant decrease in daytime sleepiness and an increase in readiness to change drug use in the real‐tDCS group. After replication in larger sample sizes, decreased craving, increased vigilance and motivation to change drug use in the real‐tDCS group may suggest fortification of dlPFC‐supported executive functions.